A Toolkit for Implementing Parental Depression Screening, Referral, and Treatment Across Systems - Schultz, Dana (RAND Corporation, 2012)
Many families experience the challenges of caregiver depression and early childhood developmental delays. This tool kit provides information and resources for implementing depression screening within the early intervention system, strengthening cross-system collaborations, and implementing relationship-based care that focuses on the parent-child relationship in the early intervention and behavioral health systems.